Quality management of microfilming projects - van Dormolen, Hans (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
I would like to tell you something about my work as quality manager microfilming and about the high quality standards for substitute microfilming we apply within the Dutch preservation programme Metamorfoze. Let me start with going back in time a bit. To be precise, to the year 1870. In this year, William Henry Jackson went riding into the hills of Wyoming, USA. Jackson was the chief photographer for the Hayden expedition. The aim of the Hayden expedition was to record the area as minutely as possible, in order to convince politicians to turn this area into a national park. There were two Hayden expeditions: in 1870 and in 1871. For both of these expeditions William Henry Jackson was the chief photographer. In 1872, the area was indeed proclaimed a national park as a result of the expeditions. And the pictures William Henry Jackson took played an important role in this US government decision. The reason I'm telling you this is not because I want to chat about the beautiful environment of Yellowstone National Park, nor do I want to emphasize the fact that it was quite an achievement that William Henry Jackson was travelling into the Wild West on horseback and coach without breaking the glass negatives he used. It's because I would like to focus your attention on the fact that today we still have access to these photographs made by Jackson and many others of his colleagues from the early days of photography, due to the excellent conditions under which these materials have been kept all this time. Without any doubt, these photographs have an important cultural and historical value.